Attitudes toward science among grades 3 through 12 Arab students in Qatar: findings from a cross-sectional national study. Issue 4 (3rd March 2016) - Said, Ziad; Summers, Ryan; Abd-El-Khalick, Fouad; Wang, Shuai
ABSTRACT: This study assessed students' attitudes toward science in Qatar. A cross-sectional, nationwide probability sample representing all students enrolled in grades 3 through 12 in the various types of schools in Qatar completed the 'Arabic Speaking Students' Attitudes toward Science Survey' (ASSASS). The validity and reliability of the 32-item instrument, encompassing five sub-scales, have already been shown to be robust. The present analysis focused on responses from 1978 participants representing the students who completed the ASSASS in Arabic. Descriptive statistics were computed and a competing pair of multiple indicators multiple causes models is presented that attempt to link patterns in students' responses to the ASSASS with a set of indicators. The final model retained student age, gender, nationality (i.e. Qatari vs. Non-Qatari Arab), and school type as indicators. Findings from this study suggest that participants' attitudes toward science decrease with age, and that these attitudes and related preferences are influenced by students' nationality and the type of school they attend. Equally important, the often-reported advantages for male over female precollege students in terms of attitudes toward science were much less prominent in the present study.